Icons of contemporary childhood: a visual and lexicogrammatical investigation of toy advertisements - Almeida, Danielle Barbosa Lins de (2006)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.